On the performance of cryptocurrency funds - Daniele Bianchi; Mykola Babiak (Sveriges Riksbank, 2021)
We investigate the performance of funds that specialise in cryptocurrency markets and contribute to a growing literature that aims to understand the value of digital assets as investments. The main empirical results support the idea that cryptocurrency funds generate significantly alphas compared to passive benchmarks or conventional risk factors. We compare the actual fund alphas against the simulated values from a panel semi-parametric bootstrap approach. The analysis shows that the extreme outperformance is unlikely to be explained by the luck of fund managers. However, the significance of the alphas becomes statistically weaker after considering the cross-sectional correlation in fund returns.
Keywords: G12; G17; E44; C5; 330; Cryptocurrency markets; Alternative investments; Fund management; Bootstrap methods